The effect of proprioceptive training in the prevention of tibiotarsal injuries - Estorninho, Ana (2022)
Objectives – To evaluate and compare the effectiveness of three different types of proprioceptive training and their relationship in reducing the incidence of ankle sprains in male youth soccer players. Method – Muscle strength in tibiotarsal joint and proprioceptivity were evaluated and compared between three groups, with supervised proprioceptive training (GE), another unsupervised (GC1), and another with technical gesture training (GC2) over a nine-week period, two to three times per week. Results – Both GE and GC1 found significant increases (p<0.01) in proprioceptivity compared with GC2. Conclusion – The results suggest that after a short period of proprioceptive exercise, athletes improve their proprioceptivity but not necessarily tibiotarsal joint muscle strength. According to the study, supervision does not have an impact on training effectiveness.